Autogiros: Review and Classification - Tsvetomir Gechev; Krasimir Nedelchev; Ivan Kralov (Aerospace)
The article reviews autogiros, concentrating on their flight history, development, application, flight principle, components, and advantages over other aircraft. Firstly, the history of autogiros is presented, focusing on breakthrough inventions and clarifying their significance for overall rotorcraft development. Then, contemporary scientific research on the autogiro is reviewed in detail, and the available research gap is determined. The flight principle and technical fundamentals of autogiros are also briefly discussed, and a comparison between autogiros, helicopters, and fixed-wing aircraft is performed. Autogiros’ applications for civil, military, and mixed purposes are pointed out and schematically presented. The main part of the article comprises an overview of the different components and systems in the structure of the reviewed aircraft, including the main rotor, propeller, engine, cockpit, and others. Additionally, a comprehensive classification mostly concerning contemporary and homologated autogiros is described and schematically presented. Experimental and compound gyroplane designs are also examined and marked in the classification. The aircraft are categorized depending on the main structure type, mast availability, number of seats, number of rotors and rotor blades, rotor and mast position, propeller and tail type and position, pre-rotator type, and power source. The idea of different autogiro variants presented in the classification is enhanced with visual examples. This work is an addition to the efforts of promoting autogiros and research on them. It offers complete information regarding the aircraft and could serve as a kind of starting point for engineers in the design process of such types of flying machines.